Synthesis and characterization of graphene - based biomedical sensors - Jay Ganesh A / l Kripakaran (2023)
For this research, the Polyvinyl fluoride (PVDF) membrane is coupled with reduced Graphene Oxide film to produce samples of different constituents. With this, the PVDF – RGO nanocomposite is tested for its dielectric properties and characterization to prove the structure. With that, reduced Graphene Oxide is prepared in separate volumes and mixed with the N – N, Dimethylformamide (DMF) solvent through ultrasonication to act as a binder and is then, correspondingly mixed with a mixture of PVDF powder with DMF solvent in an ultrasonicator. This composition is prepared in different samples with different composition as to prepare for film-casting and then stripped into thin films and prepared to be inserted into an oven for evaporation process to take place. The dried nanocomposite PVDF – RGO films are then characterized with Scanning Electron Microscope (SEM), XRD (X-ray Diffraction) for its microstructural breakdown and surface morphology and shows that highest peak has stronger bonds of the PVDF-RGO nanocomposite. Particle shape under the microscope for SEM has been obtained for magnification of 20000x, 50000x and 100000x with dispersion of electron for 5.0Kv. The electrochemical impedance spectroscopy (EIS) is utilized with a Gamry Potentiostat electrochemical set up with the Gamry software, to measure for the conductivity and capacitance value of the nanocomposite carbon film. The conductivity has been portrayed by generated Nyquist plots and the higher content of RGO in the RGO/PVDF nanocomposite carbon film is proven to have an increasing conductivity in the film as determined by EIS with parameters of an open circuit in H2SO4, sulfuric acid (pH 2.87) , with frequency of (100Hz- 100 KHz) and with the conductivity formula. As well as for the capacitance value for the thin films, the Cyclic Voltammetry method is used from the EIS configuration to show the charge and discharge capabilities of the nanocomposite carbon film. With these tests for electrical properties, the investigation is done to conclude that graphene helps to strengthen and increase the sensor quality and real-time usage and satisfies the